Sinter-free transferring of anodized TiO2 nanotube-array onto a flexible and transparent sheet for dye-sensitized solar cells - Kuo, Yu-Yen; Chien, Chao-Hsin (Electrochimica acta, 2013)
[Display omitted] ► A sinter-free method to transfer TiO2 nanotube onto plastic sheet was proposed. ► Transparent conductive oxide on nanotubes exhibited efficient charge collection. ► Hydrothermally treated nanotubes inhibited recombination in plastic solar cell. ► Nanotubes on a plastic sheet achieved 5.41% power conversion efficiency. A sinter-free method to transfer anodized TiO2 nanotube-arrays to a polyethylene terephthalate (PET) sheet is proposed. Since the anodized nanotube-array was crystallized independently before transferring to the PET, the internal charge transport resistance and the charge recombination rate are unchanged for the nanotubes on the PET sheet, and no high temperature sintering process is required. With hydrothermal treatment, the dye sensitized solar cell fabricated utilizing a low temperature bonded nanotube/PET as a photoelectrode exhibits a power conversion efficiency of 5.41%, which is only 0.87% lower than the power conversion efficiency of the solar cell using nanotubes bonded on a conductive glass through high temperature processes.